The Use of Blogs in English Language Learning: A Study of Student Perceptions - Gurleen Ahluwalia; Deepti Gupta; Deepak Aggarwal (Profile Issues in Teachers' Professional Development, 2011)
In this article we present an investigation that focused on the students' perception of using Blogs as a means to supplement in-class language learning activities. Blogs are easy to manage and enable students to publish their work in a chronological manner. They help students to engage in online exchanges and promote learner autonomy. This study evaluates a language laboratory program in which forty-two first year engineering students from a college in India were introduced to blogs and instructed to use them for recording their laboratory work. Data collection reveals that despite encountering some difficulties, students had an overall positive attitude towards using blogs in their learning of English. A follow-up study was conducted a year after the initial study and the results supported the original findings.